2013
DOI: 10.1111/apel.12024
|View full text |Cite
|
Sign up to set email alerts
|

Regional determinants of life insurance consumption: evidence from selected Asian economies

Abstract: The life insurance industry in developing Asian economies is underdeveloped compared with global standards. The low market penetration is attributed to full or partial government ownership and entry restrictions on foreign insurers. Regulatory changes and adoption of liberal policies have aided the growth of the life insurance industry in the past decade. At the same time, economic and social factors were expected to promote insurance awareness and consumption. In this context, the paper analyses the factors e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 71 publications
(77 reference statements)
5
61
0
2
Order By: Relevance
“…From Table 4 we can learn that this research has shown that incomes do have a significant and positive impact on demand for life insurance, but much more than GDP. Many authors have shown in their researches that there is a significant and positive impact of incomes on demand for life insurance, such as Sen and Madheswaran (2013), Dragos (2014), Feyen et al (2011 and others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Table 4 we can learn that this research has shown that incomes do have a significant and positive impact on demand for life insurance, but much more than GDP. Many authors have shown in their researches that there is a significant and positive impact of incomes on demand for life insurance, such as Sen and Madheswaran (2013), Dragos (2014), Feyen et al (2011 and others.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sen (2007) estimated that there is a certain impact of GDP, GDS (gross domestic savings) per capita, urbanization, adult literacy, life expectancy at birth, mortality rate, inflation, real interest rate and the price of insurance on the demand for life insurance in Asian countries, and showed that there is a significant positive relation between life insurance premium and gross domestic savings, income per capita and financial development of the country, while inflation has a negative impact on life insurance. Sen and Madheswaran (2013) analyze the factors explaining life insurance demand in 12 Asian economies too. The results suggest that income, inflation, interest rate, and the youth dependency ratio are significant determinants of life insurance consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical researches have mainly employed aggregate market and economy level data in examining the effect of income on non-life insurance consumption, due to the difficulty in accessing micro-based income statistics. Studies by Sen et al (2013), Han et al (2010) and Beck et al (2003) postulate that the income is positively related to the insurance development. The higher the level of income, will lead to higher demand in non-life insurance, in order to protect the acquired property.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to secure retirement days in a financial way, or in order to secure their successors in case of their own early death, it can be concluded that population aging may have a positive impact on life insurance demand. Sen and Madheswaran (2013) analysed determinants of life insurance consumption in Asian economies and found that youth dependency ratio was significant determinant of life insurance consumption. Lester, and Rocha (2011), consider that the reason of the positive impact on demand for life insurance is the necessity of employed parents to secure their children against the risk of parents' early death.…”
Section: Literature Reviewmentioning
confidence: 99%